2021
DOI: 10.26599/bdma.2020.9020016
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of COVID-19 confirmed, death, and cured cases in India using random forest model

Abstract: A novel coronavirus (SARS-CoV-2) is an unusual viral pneumonia in patients, first found in late December 2019, latter it declared a pandemic by World Health Organizations because of its fatal effects on public health. In this present, cases of COVID-19 pandemic are exponentially increasing day by day in the whole world. Here, we are detecting the COVID-19 cases, i.e., confirmed, death, and cured cases in India only. We are performing this analysis based on the cases occurring in different states of India in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(71 citation statements)
references
References 5 publications
(7 reference statements)
0
53
0
Order By: Relevance
“…Upon close observation of the characteristics of the other models, it became clear that a simpler model such as logistic regression (F1 score = 0.51) cannot capture the complexity of the dataset, even after selecting the best features and tuning the hyperparameters. In various other studies with similar models ( Prakash, 2020 ; Gupta V. K. et al., 2021 ), it was observed that logistic regression underperformed. In our study, random forest, multilayer perceptron, XGBoost, and SVM performed much better and had similar scores, so we can use the results of the four combined to arrive at a prediction.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Upon close observation of the characteristics of the other models, it became clear that a simpler model such as logistic regression (F1 score = 0.51) cannot capture the complexity of the dataset, even after selecting the best features and tuning the hyperparameters. In various other studies with similar models ( Prakash, 2020 ; Gupta V. K. et al., 2021 ), it was observed that logistic regression underperformed. In our study, random forest, multilayer perceptron, XGBoost, and SVM performed much better and had similar scores, so we can use the results of the four combined to arrive at a prediction.…”
Section: Discussionmentioning
confidence: 89%
“…To avoid information leaking into the test set and overfitting of data, nested CV effectively uses a series of different train–test set splits in each iteration. Nested CV is the preferred way to evaluate and compare tuned ML models and has been used before in clinical settings ( Gupta V. K. et al., 2021 ). Figure 2 demonstrates the workflow of the nested CV algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…The main limitation of the study is that we analyze, due to lacking data, only 16 European countries. However, unlike previous studies are limited in size examining just a single country 36 38 , 40 , our goal is to use the data from 16 European countries to analyze with ML techniques the global effect of different health system characteristics on COVID-19 lethality during the early days of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, ELM tends to present fewer optimization constraints, greater scalability, superior results for generalization performance, and lower learning speed concerning the others models. Gupta et al [2021] analyzed different cases of COVID-19 in India (confirmed, killed, and recovery), using machine learning models: Random Forest, Linear Model, SVM, Decision Tree e Neural Network. The results revealed that the Random Forest presented a superior performance compared to the other evaluated models.…”
Section: Related Workmentioning
confidence: 99%